2014
DOI: 10.1097/wnr.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

HIV transactivator of transcription enhances methamphetamine-induced Parkinson’s-like behavior in the rats

Abstract: Abuse of methamphetamine (MA) increases the risk of infection of HIV-1, induces considerable neurotoxicity in several brain regions, and impairs the motor and cognitive function in individuals. HIV-1 transactivator of transcription (Tat) has also shown the potent capability to induce neuronal death and impaired brain function. The present study aims to study the synergistic effect of MA and Tat on cytokine synthesis in substantia nigra, striatal dopamine content, and behavioral performance in the rats. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Some patients with HIV dementia develop acute onset Parkinsonism and dystonia when treated with dopamine receptor antagonists (Hriso et al, 1991), and patients on cART can also develop parkinsonism (Tisch and Brew, 2009). In methamphetamine-treated rodents, an intra-nigral infusion of 10 μg/μL (approximately 1 mM) Tat was shown to exacerbate Parkinson-like locomotor deficit (Liu et al, 2014). This is consistent with reports showing methamphetamine-induced behavioral sensitization were enhanced in HIV-1 Tg rats (Kass et al, 2010).…”
Section: Dopaminergic Neurotransmission Hiv Infection and Tatmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients with HIV dementia develop acute onset Parkinsonism and dystonia when treated with dopamine receptor antagonists (Hriso et al, 1991), and patients on cART can also develop parkinsonism (Tisch and Brew, 2009). In methamphetamine-treated rodents, an intra-nigral infusion of 10 μg/μL (approximately 1 mM) Tat was shown to exacerbate Parkinson-like locomotor deficit (Liu et al, 2014). This is consistent with reports showing methamphetamine-induced behavioral sensitization were enhanced in HIV-1 Tg rats (Kass et al, 2010).…”
Section: Dopaminergic Neurotransmission Hiv Infection and Tatmentioning
confidence: 99%
“…Similarly, in SH-SY5Y (neuroblastoma) cells, Tat and methamphetamine together induce a small but significant increase in apoptosis (Qi et al, 2011). In methamphetamine treated rats, where Tat was delivered directly to the substantia nigra, Tat potentiated methamphetamine induced dopamine deficits in the striatum and enhanced deficits in dopamine-driven behaviors such as the rotarod and open field tests (Liu et al, 2014). Rodents treated with both Tat and methamphetamine show 60% – 78% reductions in the basal ganglia dopamine levels, particularly striatal dopamine levels.…”
Section: Tat and Psychostimulant Abusementioning
confidence: 99%
“…We saw no observable effect of Tat on rotarod performance for either strain of mice, but a significant effect of morphine (Figure 4.6). Studies which have looked at the effect of HIV or its viral proteins on rotarod performance have been quite varied in their results with some studies finding significant impairment in accelerated rotarod performance [409,[414][415][416][417], and some studies finding no differences [214,396,399,[418][419][420], as we have here. There were, however, two significant differences between those studies and the ones performed here.…”
Section: Discussionmentioning
confidence: 62%
“…As such, glutamate uptake and dopamine release from these neurons are key aspects of function. One study on the effect of Tat and methamphetamine in rat striatal neurons showed that the treatment lead to striatal dopamine deficit which contributed to the manifestation of motor impairment [416]. The evaluation of neuronal viability performed here also requires further exploration into the mechanisms of neuronal death whether apoptosis dependent or independent pathways.…”
Section: Chapter 5: Final Conclusion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation